Espectroscopia Raman amplificada por superfície associada à cromatografia em camada delgada para análise de amostras alimentícias - Soares, Frederico Luis Felipe (2018)
Surface enhancement Raman spectroscopy (SERS) presents the advantages of conventional Raman spectroscopy with the possibility to detect compounds in low levels due to the enhancement on Raman intensity, generated by the molecule-nanoparticle system. Thin-layer chromatography (TLC) is a fast and easy separation technique, that can be coupled to several analytical techniques in order to identify compounds. TLC-SERS is a relatively new technique, with only a few works published; however it presents the advantages of both techniques synergically. The use of nanoparticles adsorbed onto the TLC plate enables to obtain Raman spectra of the separated compounds even in low concentrations. Therefore, this work proposes the use of TLC-SERS in three different application of food interest: product authentication, food safety and stability studies. 1) In product authentication, it was analyzed Pilsner beer samples in order to obtain pattern recognition related to brand and brewery. Samples were prepared in TLC plates and sprayed with gold nanoparticle to promote SERS analysis regarding the elution line of the target analytes. The obtained results were compared by two chemometric methods of data decomposition and signal recovering: multivariate curve resolution (MCR) and independent component analysis (ICA). From the obtained chromatographic peaks was possible to perform fingerprint analysis and identify clustering pattern concerning sample brand and brewery location. 2) As food safety application, the aim was to develop and optimize an analytical methodology to quantify two veterinary drugs (sulfamethoxazole and trimethoprim) in bovine milk. Central composite design was applied evaluating NaCl concentration and nanoparticles pre-concentration to optimize the analytical signal. The hyperspectral images obtained from TLC-SERS were processed using different chemometric methods. For trimethoprim, it was obtained recoveries of 82 – 112% in milk samples. Due to the high complexity of the samples, it was not possible to obtain reliable quantitative values for sulfamethoxazole. 3) For the stability study, it was kinetically assessed one red wine sample under different degradation conditions. For this, it was used a 2³ design of experiments varying pH, dissolved O2 and the presence of anti-oxidant agent. Samples were left in three stocking temperatures (4, 24 and 40 °C) and evaluated during 45 days. SERS chromatograms were analyzed using ICA, and from the chromatographic profile, it was possible to perform ANOVA-PCA where it was identified temperature and the presence of anti-oxidant agent as the most significant variables.